EU competition law and illegal/abusive pricing - Rodger, Barry (Henry Stewart Talks, 2010)
Competition Law Limitations on Abusive Pricing Strategies, Article 102 TFEU and abusive conduct, Establishing Dominance: Market Shares, Consideration of the case-law in relation to predatory pricing, selective above-cost pricing and loyalty/fidelity rebates and discounts, The EU Commission's Enforcement Priorities, Summary of the law on abusive conduct and exclusionary pricing